Conflits d’usage des petits barrages pastoraux à Ferkessédougou, Nord de la Côte d’Ivoire: la difficile sédentarisation des éleveurs Peuls - Michaël N’goh Koffi YOMAN; Raphaël Kouadio OURA; Arsène DJAKO (European Scientific Journal, ESJ, 2016)
n the mid 1970s, the Ivorian State developed a great project of pastoral hydraulic construction to settle and reduce conflicts between breeders and farmers in the North of the country. More than 300 small dams were then built, among them 20 in the department of Ferkessedougou. However, today the small dams banks are gradually colonized by garden crops. This state of affairs prevents the livestock to get access to water places and creates conflicts between the users due to the damage caused by the animals to crops. This article analyzes the conflicts about the use of small dams that hinder the settlement of Peul breeders in the department of Ferkessedougou. Some questionnaire surveys about 19 small dams were conducted from 2014 to 2015 next to 58 senoufo breeders, 55 gardeners, 36 peul breeders and 65 herdsmen. Moreover, the members of various small dam management committees, village committees for conflict resolution and the administrative authorities were interviewed in conducting the surveys to obtain qualitative data.